2004
DOI: 10.1291/hypres.27.7
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Response of the Renin-Angiotensin System and Nitric Oxide Synthesis Related to Sodium Sensitivity in Immunoglobulin A Nephropathy

Abstract: Sodium sensitivity of blood pressure appears before hypertension in immunoglobulin A nephropathy, as glomerulosclerosis and interstitial damage progress. To find whether this sensitivity is related to NO and the renin-angiotensin system, we examined 39 such patients without hypertension after they followed a diet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…15 Similar results have also been reported in Dahl salt-sensitive hypertensive rats, 16 which show reduced intrarenal NO levels. 5 The present finding that patients with type 2 diabetic nephropathy display reduced urinary excretion of NOx and increased salt sensitivity of BP, combined with results from previous studies, 2,4,7,9,15,16 is consistent with the concept that salt sensitivity of BP is induced by decreased intrarenal NO bioactivity in patients with diabetic nephropathy. We observed that treatment with an ARB restored reduced urinary renal NOx excretion in patients with type 2 diabetic nephropathy and microalbuminuria.…”
Section: Discussionsupporting
confidence: 90%
“…15 Similar results have also been reported in Dahl salt-sensitive hypertensive rats, 16 which show reduced intrarenal NO levels. 5 The present finding that patients with type 2 diabetic nephropathy display reduced urinary excretion of NOx and increased salt sensitivity of BP, combined with results from previous studies, 2,4,7,9,15,16 is consistent with the concept that salt sensitivity of BP is induced by decreased intrarenal NO bioactivity in patients with diabetic nephropathy. We observed that treatment with an ARB restored reduced urinary renal NOx excretion in patients with type 2 diabetic nephropathy and microalbuminuria.…”
Section: Discussionsupporting
confidence: 90%
“…Benign nephrosclerosis may be superimposed with IgAN. Hypertension is a well known risk factor for renal prognosis (4,5,(22)(23)(24). In our study, we histopathologically showed that vascular lesions, rather than mesangial cell proliferation, play an important role in glomerular sclerosis.…”
Section: Discussionsupporting
confidence: 51%
“…The study was finally composed of 41 patients, including 35 who we had studied previously. 16 Table 1 shows the baseline characteristics of the patients.…”
Section: Methodsmentioning
confidence: 99%